Perancangan Prototipe Pembangkit Photovoltaic 9x10 WP Berbasis Cluster String Menggunakan Algoritma Smart Controller - Nuansa, Rangga Gilang; Rajagukguk, Antonius (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
There are several problems that can interfere photovoltaic performance in large scale. Shading effect on PV arrays causes reduced absorption of solar radiation and increased temperature on modules of PV arrays. The reduced absorption of solar radiation results decreaseing voltage on PV String and disrupts performance of PV array system. This study designs a small miniature of capacity PV farm consists of 10 wattpeak PV from 9 modules that arranged into 3 strings erach string consists of 3 PV modules. This study uses a series of bypass diodes and Blocking diodes. Using this bypass diode causes voltage among PV modules to be different while using Blocking diode causes the voltage among PV strings to be different. The aim of research is to increase power generated by PV farm circuit by Clustering the String PV farm area that is covered by shadows. This Clustering is based on classification of voltage readings on each PV farm String. Voltage in Cluster1 is 42V to 58V. While voltage in cluster2 is 21V to 41V and 9v in cluster3 From simulation combination of Shading 220, Shading 210 Shading 100 Shading 011 are 11.1%, 22.2%, 33.3% and 44.4%.respectively using dummy load in process sensing voltage on String is to ensure that electric current flows in a closed circuit so that bypass diode can work when one module is shaded. The results of this study indicate that using Cluster Method Combination can improve the harvesting of power in photovoltaics under shadow. It can be concluded that using Cluster string method can increase power up to 70%. Keywords: Shading , voltage, photovoltaic, clustering, dummy load, PV farm